Photogrammetric Outcomes of Primary Nasal Correction in Unilateral Cleft Lip Patients: Early Childhood Results From a Single Surgeon's Experience. Issue 1 (January 2020) - Nunez-Villaveiran, Teresa; Fahradyan, Vahe; McNinch, Neil L.; Valentine, Ashley; Larson, Heather; Murthy, Ananth S.
Abstract : Background: Concerns of nonlasting results and potential nasal growth damage precluded cleft nasal correction at the time of initial cleft lip repair. Our goal was to evaluate the outcome of primary cleft nasal correction in our patients with unilateral cleft lip. Methods: A retrospective review of patients with complete and incomplete unilateral cleft lip who underwent primary cleft nasal correction from 2010 to 2017 by the same surgeon was performed. The cleft-to-noncleft nostril height, width, one-fourth medial part of nostril height, nasal sill height, and nostril area ratios, as well as inner nostril height-to-width ratios were determined from standard basilar view photographs taken in different time points (T1, <3 months; T2, 3–12 months; T3, 12–36 months; and T4, >36 months after surgery). A 5-point visual analog scale (1 = worst, 5 = best) was used to assess each patient's nose appearance. Results: Seventy-two patients were identified (66.7% male, 51.3% with a complete cleft lip). Average visual analog scale scores T1–T4 were 3.88 ± 0.85, 3.72 ± 0.93, 3.54 ± 0.99, and 3.40 ± 0.71, respectively. Intraclass correlation ranged from 0.61 to 0.94. A significant decrease [mean difference (SD)] was found for cleft-to-noncleft nostril width ratio [0.15 (0.18)] from T1 to T2, and an increase for one-fourth medial height ratio [−0.09 (0.07)] and for inner nostril height-to-width ratio in the noncleft side [−0.23 (0.25)] from T1 to T3. Thirteen patients required secondary surgical revision. Conclusion: Based on photogrammetry, primary cleft nasal correction in our patients with unilateral cleft lip achieved acceptable and stable outcomes during early childhood.